PENEGAKAN HUKUM DALAM MENCARI KEBENARAN MATERIIL KAITANNYA DENGAN TEMPAT KEJADIAN PERKARA DENGAN REKONSTRUKSI DI WILAYAH HUKUM HUKUM POLREST SAMARINDA - JUNAEDI, MUHAMMAD (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe relationship between reconstruction and crime scenes is to justify the information of suspects made by investigators in the context of criminal activity investigations to suit the actual situation at the scene. In practice, reconstruction is not done at the actual crime scene. This is solely done for the security of the suspect himself to avoid public tantrums. In addition to that, it is also to minimize the minimum cost of reconstruction, especially if the scene where the reconstruction will be held is outside the city. But if the crime scene is not outside the city, the reconstruction will still be carried out at the actual crime scene. If the crime scene is not known with certainty, then the efforts undertaken are: Conducting actions by investigation which is a technique of investigation so that criminal cases are revealed, where with this investigation technique will be obtained answers to questions in the field of criminal investigation; Conducting interrogation activities against incident reporters and requesting information from patient witnesses, expert witnesses and witnesses who knew the first criminal case. Although there are regional differences between the crime scene and the area where the victim was foundÂ